Primary cilia are critical for tracheoesophageal septation - Avery Fitzsimons, Lindsey; Tasouri, Evangelia; Willaredt, Marc August; Stetson, Daniel; Gojak, Christian; Kirsch, Joachim; Gardner, Humphrey A. R.; Gorgas, Karin; Tucker, Kerry L. (Developmental dynamics, 2023)
Introduction Primary cilia play pivotal roles in the patterning and morphogenesis of a wide variety of organs during mammalian development. Here we examined murine foregut septation in the cobblestone mutant, a hypomorphic allele of the gene encoding the intraflagellar transport protein IFT88, a protein essential for normal cilia function. Results We reveal a crucial role for primary cilia in foregut division, since their dramatic decrease in cilia in both the foregut endoderm and mesenchyme of mutant embryos resulted in a proximal tracheoesophageal septation defects and in the formation of distal tracheo(broncho)esophageal fistulae similar to the most common congenital tracheoesophageal malformations in humans. Interestingly, the dorsoventral patterning determining the dorsal digestive and the ventral respiratory endoderm remained intact, whereas Hedgehog signaling was aberrantly activated. Conclusions Our results demonstrate the cobblestone mutant to represent one of the very few mouse models that display both correct endodermal dorsoventral specification but defective compartmentalization of the proximal foregut. It stands exemplary for a tracheoesophageal ciliopathy, offering the possibility to elucidate the molecular mechanisms how primary cilia orchestrate the septation process. The plethora of malformations observed in the cobblestone embryo allow for a deeper insight into a putative link between primary cilia and human VATER/VACTERL syndromes.